2015
DOI: 10.1371/journal.pone.0123685
|View full text |Cite
|
Sign up to set email alerts
|

TLR4/NF-κB Signaling Contributes to Chronic Unpredictable Mild Stress-Induced Atherosclerosis in ApoE-/- Mice

Abstract: ObjectiveChronic stress is an important risk factor for atherosclerotic diseases. Our previous studies have shown that chronic unpredictable mild stress (CUMS) accelerates atherosclerosis and up-regulates TLR4/NF-κB expression in apoE-/- mice. However, TLR4/NF-κB signaling whether directly contributes to the development of atherosclerosis in CUMS mice is unclear. We hypothesized that the interference of TLR4/NF-κB can ameliorate CUMS-induced inflammation and atherosclerosis in apoE-/- mice.MethodsApoE-/- mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…It has been reported that PDTC suppresses the subsequent inflammatory activation [32]. For instance, PDTC has also been shown to decrease the plasma levels of IL-1β and TNF-α in atherosclerotic subjects [33], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that PDTC suppresses the subsequent inflammatory activation [32]. For instance, PDTC has also been shown to decrease the plasma levels of IL-1β and TNF-α in atherosclerotic subjects [33], which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…[ 3 ] A correlation among glucocorticoid, chronic inflammation, and chronic-stress-induced AS has been documented. [ 4 5 ] However, most of these experiments used mice (especially apoE-/-mice) as animal models and mainly focused on the effects of stress on total lesion areas rather than on atherosclerotic vascular wall or plaque stability. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Toll-like receptors (TLRs), critical mediators in inflammatory response, participate in progression of atherosclerotic lesions. 10 TLRs could recruit and stimulate activation of nuclear factor-κB (NF-κB). 11 NF-κB functions as transcriptional factor to regulate genes involved in immune responses and cytokines production.…”
mentioning
confidence: 99%